If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -7 = 3x + 8 Reorder the terms: -7 + 10x = 3x + 8 Reorder the terms: -7 + 10x = 8 + 3x Solving -7 + 10x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + 10x + -3x = 8 + 3x + -3x Combine like terms: 10x + -3x = 7x -7 + 7x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -7 + 7x = 8 + 0 -7 + 7x = 8 Add '7' to each side of the equation. -7 + 7 + 7x = 8 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 8 + 7 7x = 8 + 7 Combine like terms: 8 + 7 = 15 7x = 15 Divide each side by '7'. x = 2.142857143 Simplifying x = 2.142857143
| 6x-(2x+8)=3x+(x+6) | | y=0-5x | | 500=55n-35n | | 4(n+4)=-2(4+2n) | | x+21=23+5x | | X^2+6=25 | | x+2.1=8.3 | | 1.5=0.8 | | -1-2(x+1)=3-2x | | 7x+9=-2x+55 | | (100-4Z)20= | | 3x+x-8=4 | | x-1=1.26 | | -12n+10=-8+2 | | 4x+8+(-3x)=20 | | 4x-1+5x+2=90 | | 8(2n+1)=8(4n+1)+5 | | 4x-1+5x+2=180 | | -2+3(x-1)=-5+3x | | -5y=2.55 | | f(x)=x+4f(-7) | | 4x+yminush=10y+u | | 4x-1+5x+2+8x=7 | | 4(X-2)=6-(3-2X) | | 10x^2+2*x-26=4 | | x+2=(sqrtx+7)+2 | | -63=4j(j-8) | | f(x)=6x-6f(10) | | 8(x+7)-8x=-8x+40 | | (x+38)+(x)=180 | | -16t^2-12t+52=0 | | 2n=(n+9) |